The organic chemistry of drug design and drug action - Silverman, Richard B.; Holladay, Mark W. (San Diego Academic Press, 2015)
The Organic Chemistry of Drug Design and Drug Action, Third Edition, represents a unique approach to medicinal chemistry based on physical organic chemical principles and reaction mechanisms that rationalize drug action, which allows reader to extrapolate those core principles and mechanisms to many related classes of drug molecules. This new edition includes updates to all chapters, including new examples and references. It reflects significant changes in the process of drug design over the last decade and preserves the successful approach of the previous editions while including significant changes in format and coverage. This text is designed for undergraduate and graduate students in chemistry studying medicinal chemistry or pharmaceutical chemistry; research chemists and biochemists working in pharmaceutical and biotechnology industries.--Provided by publisher.
Introduction -- Lead discovery and lead modification -- Receptors -- Enzymes -- Enzyme inhibition and inactivation -- Dna-interactive agents -- Drug resistance and drug synergism -- Drug metabolism -- Prodrugs and drug delivery systems.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Pharmaceutical chemistry; Bioorganic chemistry; Molecular pharmacology; Drugs -- Design; Electronic books